Perchè indagare sull'empatia in musica (Materiali di Estetica. Terza serie, 2025)
This introduction outlines the premises and experiences that inspired this issue of Materiali di Estetica. It also places the "Sintonie" project within the context of the growing scientific, educational, and musicological research at Italian conservatories, thanks to new synergies with universities and research institutions.
Keywords: conservatory; synergies; performers; well being